A review of past changes in extratropical cyclones in the northern hemisphere and what can be learned for the future. (19th September 2020) - Raible, Christoph C.; Pinto, Joaquim G.; Ludwig, Patrick; Messmer, Martina
Abstract: Extratropical cyclones, a major phenomenon of the mid‐latitude atmospheric dynamics, show strong variability over a range of time scales. Future projections hint at an increase of cyclonic intensity and the associated precipitation, an important fact to be considered when developing future risk assessments. This review presents a first overview of studies which (a) puts the current variability and projected future climate changes of extratropical cyclone characteristics in a long‐term perspective, (b) shows connections to natural external forcings, and (c) deepens our understanding of cyclone intensification processes for past climate periods. We summarize the current state of knowledge for two periods in the past—the last millennium and the Last Glacial Maximum (LGM, 21, 000 years ago). For these two periods, the sparse information from paleo proxy archives are compared to climate modeling results on global and regional scales. For example, strong changes of the climate mean state, induced by orbital forcing and associated feedbacks, show strong effects on different cyclone characteristics, for example, a southward shift of the storm tracks over the North Atlantic during the LGM. Other findings indicate that dynamic processes could play at least an equally important role as thermodynamic processes for the variations of cyclone‐induced precipitation. This is in contrast to the projected future changes in cyclone‐related precipitation, which are driven primarily by thermodynamic processes. The review demonstrates how a paleoclimatic view can foster an extended process understanding and be instrumental to better understand future changes in extratropical cyclones and associated characteristics. This article is categorized under: Paleoclimates and Current Trends > Modern Climate Change Abstract : Schematic of the storm tracks, atmospheric circulation relevant for extratropical cyclones, and hydrological implications of extratropical cyclones comparing present day (PD) with the Last Glacial Maximum (LGM) based on model evidence. The compilation is based on several modeling studies using different models. We only include features where models agree on. The dashed arrow between Iceland and Scandinavia is only based on limited model evidence. Note that we focus on the winter, where extratropical cyclones are mostly pronounced, and, thus, most of the studies focus on.